Development of Thalamocortical Connectivity during Infancy and Its Cognitive Correlations - Alcauter, Sarael (Society for Neuroscience, 2014)
Although commonly viewed as a sensory information relay center, the thalamus has been increasingly recognized as an essential node in various higher-order cognitive circuits, and the underlying thalamocortical interaction mechanism has attracted increasing scientific interest. However, the development of thalamocortical connections and how such development relates to cognitive processes during the earliest stages of life remain largely unknown. Leveraging a large human pediatric sample (N = 143) with longitudinal resting-state fMRI scans and cognitive data collected during the first 2 years of life, we aimed to characterize the age-dependent development of thalamocortical connectivity patterns by examining the functional relationship between the thalamus and nine cortical functional networks and determine the correlation between thalamocortical connectivity and cognitive performance at ages 1 and 2 years. Our results revealed that the thalamus–sensorimotor and thalamus–salience connectivity networks were already present in neonates, whereas the thalamus–medial visual and thalamus–default mode network connectivity emerged later, at 1 year of age. More importantly, brain–behavior analyses based on the Mullen Early Learning Composite Score and visual–spatial working memory performance measured at 1 and 2 years of age highlighted significant correlations with the thalamus–salience network connectivity. These results provide new insights into the understudied early functional brain development process and shed light on the behavioral importance of the emerging thalamocortical connectivity during infancy.